MEDIAMUSIC ORIGINS - Chernyshov Alexander V. (Mediamuzyka, 2012)
The article investigates the origins of music in electronic regular broadcasting, which conditions have appeared in the XIX century. They stand out in the "telephone concerts", "phonograph concerts" and the proto-sound films (T.Edison, W.Dickson, Ch.Pathé, O.Messter). In the early twentieth century, a clear prototype of mediamusic playing by the music of "silent" films, which has been divided on the on-screen and offscreen sound layers, the method of compilation, the basics of synchronization between musical sound and off-music montage-structures. In addition, the origins of music of electronic mass media can be regarded as attempts to understand the "musical" noise features, which subsequently materialize in the phenomenon of "noisemusic" of media audio-score (L.Russolo, Ars.Avraamov, D.Vertov, W.Ruttmann, N.Voinov, P.Schaeffer). Are considered Russian, European and North American experiences.